2012
DOI: 10.1159/000339285
|View full text |Cite
|
Sign up to set email alerts
|

Iron Sucrose Impairs Phagocytic Function and Promotes Apoptosis in Polymorphonuclear Leukocytes

Abstract: <b><i>Background:</i></b> With the recent implementation of bundling reimbursement policy, the use of intravenous (IV) iron preparations for the management of anemia in the end-stage renal disease (ESRD) population has dramatically increased. Iron overload increases the risk of infections in individuals with or without kidney disease. IV iron administration in ESRD patients impairs bacteriocidal capacity of polymorphonuclear leukocytes (PMNs) against <i>Escherichia coli</i>.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 80 publications
3
36
0
Order By: Relevance
“…Findings from an in vitro study using serum samples collected from hemodialysis patients suggest that non-transferrin-bound iron observed in serum after IV iron was positively associated with bacterial growth [19]. Moreover, in a challenge test with healthy subjects, iron supplementation suppressed the phagocytic function of leukocytes against both gram-negative and gram-positive bacteria and induced cell apoptosis [20]. Recently, it was reported that a high serum ferritin level was associated with increased mortality in Japanese hemodialysis patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from an in vitro study using serum samples collected from hemodialysis patients suggest that non-transferrin-bound iron observed in serum after IV iron was positively associated with bacterial growth [19]. Moreover, in a challenge test with healthy subjects, iron supplementation suppressed the phagocytic function of leukocytes against both gram-negative and gram-positive bacteria and induced cell apoptosis [20]. Recently, it was reported that a high serum ferritin level was associated with increased mortality in Japanese hemodialysis patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…Iron administration deteriorates phagocytic function in gram-positive and gram-negative bacteria and induces apoptosis in polymorphonuclear neutrophil leukocytes [141]. Iron is also necessary for the proliferation of bacteria [142], and for this reason, the possibility of an association between iron administration and the proliferation of bacteria has been raised [143].…”
Section: Statement 3-2 *mentioning
confidence: 99%
“…Intravenous iron therapy may also entail a number of unwanted side-effects and long-term consequences including promotion of atherosclerosis, cardiovascular events, infections or cancer [11-14]. …”
Section: Introductionmentioning
confidence: 99%